2022
DOI: 10.3389/fped.2022.813614
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Nomogram for Predicting Refractory Mycoplasma pneumoniae Pneumonia in Children

Abstract: BackgroundIn children, refractory Mycoplasma pneumoniae pneumonia (RMPP) may result in severe complications and high medical costs. There is research on a simple and easy-to-use nomogram for early prediction and timely treatment of RMPP.MethodsFrom December 2018 to June 2021, we retrospectively reviewed medical records of 299 children with Mycoplasma pneumoniae pneumonia (MPP) hospitalized in Tianjin Children's Hospital. According to their clinical manifestations, patients were divided into the RMPP group and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…Dynamic monitoring of CRP levels can be used to assess the prognosis of hospitalized CAP patients 31 . In a prior investigation, CRP was found to be an independent predictor of refractory mycoplasma pneumonia in children 32 . We found that CRP was a predictor of MPP in adults and was mildly elevated in MPP adult patients, which suggested a mild inflammatory response in patients.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Dynamic monitoring of CRP levels can be used to assess the prognosis of hospitalized CAP patients 31 . In a prior investigation, CRP was found to be an independent predictor of refractory mycoplasma pneumonia in children 32 . We found that CRP was a predictor of MPP in adults and was mildly elevated in MPP adult patients, which suggested a mild inflammatory response in patients.…”
Section: Discussionmentioning
confidence: 88%
“…Nomograms, which are intuitive and visualized risk prediction models, have been widely used in recent years to predict cancer and surgical prognosis 12 14 , can rapidly and accurately identify high-risk groups and can improve the diagnostic efficacy. In the latest research, a nomogram was used to predict the occurrence of refractory Mycoplasma pneumoniae pneumonia (RMPP) in children and bronchial mucus plugs in children with MPP, and both showed good predictive performance 15 , 16 . However, few predictive models have been reported for MPP in adults.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other published papers, [40][41][42] the enrolled patients in our study differed in two points: 1) patients were confirmed as macrolide-unresponsive MPP (MUMPP); 2) patients continued to be treated with macrolide (azithromycin) after the confirmation of MUMPP without antibiotic changes. In addition, the purpose of this study is different from other studies.…”
Section: Discussionmentioning
confidence: 76%
“…In the recent 2 years, as a new type of predictive model with easy clinical application, strong discriminatory ability and high accuracy, the nomogram model has been confirmed in several retrospective studies for its validity as an early identification of RMPP. [19][20][21][22][23] However, the variability of the indicators included in different studies has led to a lack of consistency in the nomogram model, and external validation by prospective multicenter studies is needed for its clinical application.…”
Section: Hotspots and Frontiersmentioning
confidence: 99%